2021
DOI: 10.3390/nu13093263
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in Cystic Fibrosis: A Systematic Review on Prevalence and Potential Benefits

Abstract: Breastfeeding (BF) is considered the normative standard of feeding for all infants. However, the impact of BF in patients with cystic fibrosis (CF) is not completely defined. Therefore, we conducted a systematic review to evaluate BF prevalence in the CF population and its impact on anthropometric and pulmonary outcomes. We searched MEDLINE, Embase and the Cochrane Library for original articles published in English up to 4 December 2020 that report the prevalence of BF and/or any measure of association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…BF is protective against stunted growth and chronic pseudomonas infection in infants with meconium ileus 34 . Although the CFF has recommended BF since 2002, the prevalence and duration of BF in CF are decreased compared to the general population 35 . Barriers to BF in CF include stress associated with the diagnosis, malnutrition concerns, and a heavy burden of care.…”
Section: Importance Of Early Nutrition For Infants With Cfmentioning
confidence: 99%
See 1 more Smart Citation
“…BF is protective against stunted growth and chronic pseudomonas infection in infants with meconium ileus 34 . Although the CFF has recommended BF since 2002, the prevalence and duration of BF in CF are decreased compared to the general population 35 . Barriers to BF in CF include stress associated with the diagnosis, malnutrition concerns, and a heavy burden of care.…”
Section: Importance Of Early Nutrition For Infants With Cfmentioning
confidence: 99%
“…34 Although the CFF has recommended BF since 2002, the prevalence and duration of BF in CF are decreased compared to the general population. 35 Barriers to BF in CF include stress associated with the diagnosis, malnutrition concerns, and a heavy burden of care. Efforts to promote and support BF such as board-certified lactation consultants in CF clinics can be highly effective.…”
Section: Supporting Optimal Feeding Patterns For Infants With Cfmentioning
confidence: 99%
“…Most of these studies have demonstrated that the majority of people with CF recover fully and maintain their lung function despite COVID-19 infection although some individuals experience more serious disease. [60][61][62][63][64][65][66][67][68] The longer term effects of COVID-19 in people with CF remain unknown. Studies of COVID-19 in CF have consistently identified previous solid organ transplantation as a key risk factor for adverse outcomes including ICU admission and death.…”
Section: Coronavirus Disease 2019 In Cystic Fibrosismentioning
confidence: 99%